The emergence of modern hospital management and organisation in the world 1880s-1930s - Fernández Pérez, Paloma (Frontiers of management history., 2021)
The Emergence of Modern Hospital Management and Organisation in the World 1880s-1930s uses a range of empirical evidences and case studies drawn from previously unpublished archival sources to offer one of the first international comparative studies on the transformation and modernization of hospital management globally, a century ago. Focusing in the key years between the 1880s and the 1930s, when millions of people crossed the globe and created new large health care needs in the largest cities of the world, Paloma Fernández-Pérez analyzes core themes from a business history perspective, like organization, ownership and the professionalization of management, to reach a new understanding about the history of modern large scale healthcare institutions from the United States to China, with particular attention to Spain. The book analyses how varying institutional factors, as well as specific national elements, have influenced the application of Taylorist ideas about standardization, efficiency, and productivity, to large scale hospitals. It also demonstrates the complexities in the dissemination of Taylorist styles of management in large hospitals in the world, by presenting the diversity of situations and how they depended not just on national differences but also on the balance of power of interest groups in private and public hospitals.